2017
DOI: 10.1515/eko-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Comparing habitat preferences of a set of waterbird species wintering in coastal wetlands of North Africa: implication for management

Abstract: Every year, the Coastal wetlands of North Africa support an important wintering waterbird population of many Palearctic and sub-Saharan species of various contrasting habitat requirements. In this study, we describe the habitat use by24 water-obligate species wintering in a coastal wetland of the Northeastern Algeria (the wetland of Lake Tonga), highlighting thereby the ecological mechanisms that support their coexistence and their resources partitioning. The analysis of resource exploitation (Relative frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Its numbers can reach 1500 birds. The Recurvirostridae family is also represented by two species that frequent the banks of this wetland only during the summer period (Figure 4) (Elafri et al, 2017, Baaziz et al, 2011, Seddik et al, 2010, 2012. The Laridae family is very poorly represented in this wlake (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Its numbers can reach 1500 birds. The Recurvirostridae family is also represented by two species that frequent the banks of this wetland only during the summer period (Figure 4) (Elafri et al, 2017, Baaziz et al, 2011, Seddik et al, 2010, 2012. The Laridae family is very poorly represented in this wlake (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Anatids have been reported to prefer open water and floating vegetation habitats for dabbling and food resources these habitats provide them (2) . Elafri et al, (2017) (53) has also suggested that open water is a shallow habitat and provides organic matter to dabbling and diving ducks, coots and grebes. Anatids showed low presence in tall emergents during midwinter, because dense vegetative cover restricts their movement and foraging efficiency (53) , (54)(55)(56) .…”
Section: Discussionmentioning
confidence: 99%
“…Elafri et al, (2017) (53) has also suggested that open water is a shallow habitat and provides organic matter to dabbling and diving ducks, coots and grebes. Anatids showed low presence in tall emergents during midwinter, because dense vegetative cover restricts their movement and foraging efficiency (53) , (54)(55)(56) . In post winter anatids were abundant in floating vegetation due to the growth of new macrophytes which provided food.…”
Section: Discussionmentioning
confidence: 99%
“…e Common Pochard is a Eurasian duck found in a wide variety of wetlands (marshes, lagoons, lakes, artificial reservoirs, and rivers), with eutrophic to pH neutral waters, but it mostly prefers large open bodies of water with abundant emergent vegetation [8][9][10]. In Morocco, it is a winter visitor, passage migrant, and occasional to regular breeder [4,11,12].…”
Section: Introductionmentioning
confidence: 99%